The Effect of Compensation on Employee Productivity in Grand Rocky Hotel Bukittinggi - Yuliana .; Ranty Mulina Safitri; Sukma Yudistira (International Journal of Tourism, Heritage and Recreation Sport, 2020)
This study intended to determine the effect of Compensation on employee productivity at Grand Rocky Hotel Bukittinggi. This study included quantitative research with a causal associative approach. The population in the study was all employees, with a total of 118 employees. The sample in this study amounted to 54 employees with techniques stratified proportional random sampling. Data collection is done by distributing questionnaires (questionnaire) using a Likert scale that is tested for validity and reliability. Data were analyzed by simple linear regression testing through the SPSS 16.00 computer program. The results showed that: 1) Compensation of employees at Grand Rocky Hotel Bukittinggi was mostly in the unfavorable category of 40.76%. 2) Employee productivity is mostly in the bad category, 59.25%. 3) The coefficient of determination R Square is 0.132 and obtains a significance value of 0.007, which means that there is a significant influence of 13.2% between Compensation for employee productivity at Grand Rocky Hotel Bukittinggi while 86.8% is influenced by other factors not examined.